Calibration-free whole-brain CEST imaging at 7T with parallel transmit pulse design for saturation homogeneity utilizing universal pulses (PUSHUP). - Völzke, Yannik; Akbey, Suzan; Löwen, Daniel; Pracht, Eberhard Daniel; Stirnberg, Rüdiger; Gras, Vincent; Boulant, Nicolas; Zaiß, Moritz; Stöcker, Tony (Magnetic Resonance in Medicine, 2025)
PURPOSE: Chemical exchange saturation transfer (CEST) measurements at ultra-high field (UHF) suffer from strong saturation inhomogeneity. Retrospective correction of this inhomogeneity is possible to some extent, but requires a time-consuming repetition of the measurement. Here, we propose a calibration-free parallel transmit (pTx)-based saturation scheme that homogenizes the saturation over the imaging volume, which we call PUlse design for Saturation Homogeneity utilizing Universal Pulses (PUSHUP). THEORY: Magnetization transfer effects depend on the saturation B 1 rms B_1^rms . PUSHUP homogenizes the saturation B 1 rms B_1^rms by using multiple saturation pulses with alternating B 1 B_1 -shims. Using a database of B 1 B_1 maps, universal pulses are calculated that remove the necessity of time-consuming, subject-based pulse calculation during the measurement. METHODS: PUSHUP was combined with a whole-brain three-dimensional-echo planar imaging (3D-EPI) readout. Two PUSHUP saturation modules were calculated by either applying whole-brain or cerebellum masks to the database maps. The saturation homogeneity and the group mean CEST amplitudes were calculated for different B 1 B_1 -correction methods and were compared to circular polarized (CP) saturation in five healthy volunteers using an eight-channel transmit coil at 7 Tesla. RESULTS: In contrast to CP saturation, where accurate CEST maps were impossible to obtain in the cerebellum, even with extensive B 1 B_1 -correction, PUSHUP CEST maps were artifact-free throughout the whole brain. A 1-point retrospective B 1 B_1 -correction, that does not need repeated measurements, sufficiently removed the effect of residual saturation inhomogeneity. CONCLUSION: The presented method allows for homogeneous whole-brain CEST imaging at 7 Tesla without the need of a repetition-based B 1 B_1 -correction or online pulse calculation. With the fast 3D-EPI readout, whole-brain CEST imaging with 45 saturation offsets is possible at 1.6 mm resolution in under 4 min.
EVALuna2:586155